Checking the basis of intraosseous access—Radiological study on tibial dimensions in the pediatric population. Issue 10 (28th August 2020) - Capobianco, Stéphanie; Weiss, Markus; Schraner, Thomas; Stimec, Jennifer; Neuhaus, Kathrin; Neuhaus, Diego
Abstract: Background: Malposition of intraosseous needles in pediatric patients is frequently reported. Incorrect needle length and penetration depth related to the puncture site and level are possible causes. Aims: Aim of this study was to analyze anatomic dimensions of the proximal tibia in the pediatric population with respect to intraosseous needle placement and needle tip position. Methods: Plain lower leg radiographs of children aged from birth to 16 years of age were analyzed. Pretibial tissue layer, cortical bone thickness, and the diameter of the medullary cavity were measured at two different puncture levels. Data were analyzed as descriptive statistics and by polynomial regression plots and set in context to commonly used EZ‐IO ® needle lengths of 15 and 25 mm. Results: Radiographs from 190 patients (104 boys/86 girls) were included. When fully inserted to skin level, up to 10.5% of needles do not reach medullary cavity at one and 18.5% at two patient's fingerbreadths distal to tibial tuberosity. The opposite cortical wall is touched or penetrated in 16% and 25%, respectively. Up to 96% of too deep needle tip positions occur in children younger than 24 months, as do too superficial tip positions in 59%. Conclusions: Puncture level and needle length have a great influence on potential needle tip positions. Infants and toddlers are at highest risk for malpositioning. Due to relevant growth‐related differences in tibial anatomy, an age‐related and well‐reflected approach is crucial to successfully establish intraosseous access.